The past of time in Aristotle - Hüni, Heinrich (Estudios de Filosofía, 2002)
This essay aims to reconstruct the Aristotelian theory of time in eight steps, namely: 1. Mobility as the main characteristic of being; 2. life as a praxis essentially linked to speech; 3. the express relationship between time and experience of movement; 4. history and natural movement, in which the relationship and difference between these and time is discussed; 5. It seeks to show how time is properly generated, gathering what was thought in the previous steps; 6. The linguistic possibility of saying "now" is highlighted as an essential moment of understanding the generation of time; 7 an attempt is made to thematize the relationship that Aristotle establishes between time and number, and, finally; 8. the relationship between past and Time.